UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN SIKAP JUJUR PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK DI MTs AN-NUR BULULAWANG - Dewi Mawarni; Abd Jalil; Moh Eko Nasrullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study uses a qualitative research approach with qualitative descriptive methods.The purpose of this study was to describe the way of inculcating honest attitudes ofstudents, the implementation of honesty values of students, and the inhibiting faktorsto inculcate honest attitudes of students in moral aqidah subjects in MTs An-NurBululawang. In this research, the researcher acts as an instrument as well as the datacollector. The results of the research that has been carried out are 1) The way to instillhonest attitudes in students in moral aqidah subjects is by transmitting somethingaccording to the facts, not lying, not manipulating information and daring to admitmistakes; 2) The implementation of the values of honesty of the students is donethrough example, activities in the classroom and through the honesty dining program;3) The faktors that inhibit the inculcation of an honest attitude consist of internalfaktors and external faktors.